PERAN GLOBALISASI DALAM SEJARAH KEBUDAYAAN ISLAM DI INDONESIA PADA MASA KEKINIAN - Aminudin (Ta'dibiya, 2023)
This research aims to explore and analyze the historical development of Islamic culture in Indonesia today. The main focus of this research is to identify the transformation of Islamic culture, the role of Islam in everyday life, and the impact of globalization on the sustainability of Islamic culture in Indonesia. This research method involves analysis of historical documents, interviews with cultural figures, and observation of religious and cultural practices related to Islam. The research results show that Islamic culture in Indonesia today is experiencing complex dynamics. Globalization brings new influences in the form of technology, social media and lifestyle, which significantly influence the way Indonesian people understand and practice Islamic culture. On the one hand, there have been positive changes in religious interpretation and adaptation to local values. However, on the other hand, there are challenges such as moral decline, conflict of interpretations, and the loss of local cultural identity in the global flow. In this context, this research also highlights the important role of education in developing a correct understanding of Islamic culture, as well as facilitating intergenerational dialogue to maintain the continuity of cultural values. This research provides in-depth insight into the complexity of the dynamics of Islamic culture in Indonesia today, which can be the basis for public policy, educational institutions and society in building harmony and diversity in society.